Economic Conjuncture of Arctic Natural Gas in the New Geopolitical Conditions - Sergey Yu. Kozmenko; Arina S. Kozmenko (Арктика и Север, 2023)
The special military operation (SMO) organically fits into the logic of the century-long confrontation between Russia and Britain, and later — the USA, known since the late 18th century as the “Great Game”. One of the goals of the SMO on a national scale is not only to restore Russia’s dominance in the Black Sea and the Sea of Azov, but also to counteract the achievement of such a goal by NATO countries. Russia uses various sources of funding the SMO, including oil and gas revenues of the Federal budget. Natural gas, unlike oil, is not under sanctions. There is nothing to compensate for the loss of revenues from the reduction of gas exports to Europe: practically all Russian pipelines (except for the Power of Siberia-1 with a capacity of only 38 billion m3) are oriented to the West; liquefied natural gas from the Yamal LNG and Sakhalin-2 projects is contracted for many years ahead. The EU countries have nothing to compensate for the lost volumes, except coal, but only Russian coal. Europe needs gas, Russia needs currency for the SMO, so it is necessary to find a solution to the problem.